DESEMINASI HASIL PENELITIAN INTERAKSI SOSIAL DAN SIKAP MULTIKULTURALISME MAHASISWA UNIVERSITAS X DI JAKARTA - Ninawati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2023)
Building awareness of multiculturalism in a nation-state like Indonesia is not an easy endeavor, especially with the awareness that Indonesia is a country characterized by a heterogeneous society, a multicultural and multi-ethnic country. Multiculturalism not only requires living together based on the principle of diversity in diversity which is full of tolerance and harmony, but also understanding and respect for inter-cultural, inter-religious, inter-ethnic groups in fostering a societal order full of peace, tranquility and love (Shofa, 2016) . Various ways and steps are used so that this attitude of multiculturalism can grow in Indonesian society. One way is through social interaction by individuals. The process of creating a multicultural society requires a willingness to take action from the government, especially in the field of education by emphatically conveying multicultural aspects. Multicultural problems in Indonesian society need awareness to understand them. In a multicultural and multiethnic society maintaining relationships and interactions is very much needed in order to get a safe society. For this reason, maintaining good relations in order to create a safe atmosphere requires interaction that exists between its citizens. Through this dissemination activity it is introduced how social interaction occurs in order to create a good multicultural attitude among students. By holding dissemination through webinars, it is hoped - a little or a lot - to add insight or knowledge about the need for a multicultural attitude. Dissemination was carried out through an online seminar on November 30, 2022 with the topic